ROTATION PERIODS AND ACTIVITY ON RED DWARFS - Bondar', N. I. (Одеські астрономічні публікації, 2017)
Relation between duration of cycles of photospheric activity and stellar rotation are considered here for samples of dKe-dMe stars and compared with similar ones for solar-like stars. Fast and slowly rotating stars shown two sequences on the diagram. Cycle length of slowly rotating stars is close to solar and not depend on rotation, but red dwarfs with Prot < 5d show tendency to increasing of cycle time with faster rotation. Activity of fast rotating K and M dwarfs are more higher as well on photospheric level as coronal region.